Assessment of forestry parameters at single-tree level by using methods of LIDAR data analysis and processing / Avaliação de parâmetros florestais de árvores individuais utilizando métodos de análise e processamento de dados LIDAR - Andrea Barilotti (Ambiência, 2010)
AbstractIn this paper a chain of laser scanning data processing in order to automatically detect the principal forestry parameters deriving from a single-tree extraction approach is presented. The overall method was based on mathematical morphology operations to assess the cartographical position of them, as well as the height of the trees. Starting from single-extracted trees, a segmentation algorithm made it possible to classify the laser point data as a subset of crown points. For each tree, some morphometric and biometric parameters were estimated. A method to distinguish between some of principal tree species of alpine latitudes is afterwards presented. The species classification was based on the study of the single crown Gaussian curvature, from estimated differential parameters of the Taylor’s formula extended to second order terms. The experiments, carried out in the Alpine context of the North-East Italy (Friuli Venezia Giulia Region), highlighted that the percentage of tree extraction ranged between 70% and 95% in juvenile and mature forests respectively while 80% - 90% of corrected classified tree species (coniferous and broad-leaved) was obtained. Concerning the stand volume, the estimation accuracy varied between 80% and 95% in broad-leaved and coniferous stands respectively. ResumoNeste trabalho, é apresentado uma cadeia de processamento de dados de rastreamento a laser, a fim de detectar automaticamente os parâmetros florestais principais decorrentes de uma abordagem de extração de árvores individuais. O método global foi baseado em operações de morfologia matemática para avaliar a posição cartográfica, bem como a altura das árvores. A partir da extração de árvores individuais, um algoritmo de segmentação permitiu classificar os dados a laser como um subconjunto de pontos de copas. Para cada árvore, alguns parâmetros morfométricos e biométricos foram estimados. Um método para distinguir algumas das principais espécies de árvores de altitudes alpinas é apresentado depois. A classificação de espécie foi baseada em estudos da curvatura de Gaussian de árvores de copa única, de parâmetros diferenciais estimados pela fórmula de Taylor estendidos aos termos de segunda ordem. Os experimentos, realizados no nordeste da Itália (região de Friul-Veneza Júlia), destacou que o percentual de extração de árvore variou entre 70% e 95% em florestas juvenil e adulta respectivamente, enquanto 80% - 90% das espécies de árvores classificadas (coníferas e folhosas) foram obtidas. Quanto ao volume de povoamento, a precisão da estimativa variou entre 80% e 95% em povoamento de folhosas e coníferas, respectivamente.